Alkylation reactions of nitro alcohols and synthesis of miserotoxin. - Shields, Douglas Craig. (University of Ottawa (Canada), 1970)
Part I. 1(e),3(e)-Dimethoxy-2(e)-nitrocyclohexane (IV) and 3(e)-methoxy-2(e)-nitrocyclohexan-1(e)-ol (V) were prepared from 2(e)-nitrocyclohexene-1(e),3(e)-diol (II) by reaction with diazomethane in the presence of boron trifluoride. The dimethyl ether (IV) was also prepared by reaction of 2(e)-nitrocyclohexane-1(e),3(e)-diol diacetate (III) with sodium methoxide. An analogous elimination-addition reaction with sodium benzoxide yielded the dibenzyl ether (VII). Reaction of the diacetate (III) with sodium isopropoxide did not yield the diisopropyl ether and the only product isolated from this reaction was 3-acetoxy-2-nitrocyclohexene (IX). The Schmidt-Rutz dehydroacetylation of the diacetate (III) also furnished the olefin IX. 3-Methoxy-2-nitrocyclo-hexene (X) was prepared by the Schmidt-Rutz reaction of 3(e)-methoxy-2(e)-nitrocyclohexan-1(e)-ol acetate (VI). This olefin X was also prepared by dehydration of the monomethyl ether V with basic aluminum oxide and by reaction of the acetoxy olefin IX with refluxing methanol. 3-Ethoxy-2-nitrocyclohexene (XI) was similarly prepared by refluxing IX in ethanol. Part II. 3-Nitropropyl 2,3,4,6-Tetra-O-acetyl-beta-D-glucopyranoside (IV) was prepared by Koenigs-Knorr reaction of tetra-O-acetyl-alpha-D-glucopyranosyl bromide (V) with 3-nitro-1-propanol (IV) in the presence of silver oxide. Deacetylation of VI with sodium methoxide furnished 3-nitropropyl beta-D-glucopyranoside (miserotoxin) (II).
Keywords: Chemistry, Biochemistry.